2020
DOI: 10.1519/jsc.0000000000003787
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Global Positioning System Units for Measuring Distance and Velocity During Linear and Team Sport Simulated Movements

Abstract: Huggins, RA, Giersch, GEW, Belval, LN, Benjamin, CL, Curtis, RM, Sekiguchi, Y, Peltonen, J, and Casa, DJ. The validity and reliability of GPS units for measuring distance and velocity during linear and team sport simulated movements. J Strength Cond Res 34(11): 3070–3077, 2020—This experimental study aimed to assess the validity and reliability of shirt-mounted 10-Hz global positioning system (GPS) units (Polar Team Pro) for measuring total distance (TD), constant velocity (VelC), and instantaneous velocity (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 28 publications
1
35
1
2
Order By: Relevance
“…All practices and games were monitored using the Polar TeamPro system (Polar Electro Co., Woodbury, NY), which uses HR, GPS, and accelerometry technology (21). Physiological attributes of the player obtained from laboratory testing (i.e., player age, height, body mass, sex, V̇O 2 max, HRmax, and HR at ventilatory threshold) were used to program each player's monitor through the Polar TeamPro online platform.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All practices and games were monitored using the Polar TeamPro system (Polar Electro Co., Woodbury, NY), which uses HR, GPS, and accelerometry technology (21). Physiological attributes of the player obtained from laboratory testing (i.e., player age, height, body mass, sex, V̇O 2 max, HRmax, and HR at ventilatory threshold) were used to program each player's monitor through the Polar TeamPro online platform.…”
Section: Methodsmentioning
confidence: 99%
“…Biomarkers in the analysis included markers of stress (free cortisol[FCORT] and total cortisol [TCORT]), muscle breakdown or turnover (creatine kinase [CK]), inflammatory markers (interleukin-6 [IL-6]), markers of anabolism (growth hormone [GH], insulin-like growth factor-1 [IGF-1], total testosterone [TTEST], and free testosterone [FTEST]), markers of reproductive health (total estrogens [E], prolactin [PRL], and sex hormone-binding globulin [SHBG]), markers of metabolism (triiodothyronine [T 3 ] and thyroxine [T 4 ]), and nutritional markers (iron [Fe], tryptophan [TRP], glutamine [GLN], phenylalanine [PHE], and taurine [TAU]) (23).Season Training and Monitoring. All practices and games were monitored using the Polar TeamPro system (Polar Electro Co., Woodbury, NY), which uses HR, GPS, and accelerometry technology(21). Physiological attributes of the player obtained from laboratory testing (i.e., player age, height, body mass, sex, V Ȯ2 max, HRmax, and HR at ventilatory threshold) were used to program each player's monitor through the Polar TeamPro online platform.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously conducted studies on 10 Hz GPS devices have shown that this GPS device has good validity and reliability (5% CV) for total distance, linear running, and change of direction [ 15 , 16 ]. For the Polar Team Pro®️ model used in this study, the ICCs have been reported as extremely high for running less than 13.99 km/h and 14–19.99 km/h (0.99 and 0.92, respectively), and high for total distance and sprinting (>20 km/h) (0.63 and 0.65, respectively) [ 17 ].…”
Section: Match Analysismentioning
confidence: 99%
“…This technology is based on a signal concentration system of different Polar brand sensors, designed for the control and monitoring of physical activity in collective sports like soccer or basketball. This technology has been validated [31,32] and used in previous studies that registered the physical load of soccer tasks [10,19] and is currently one of the most used instruments for the quantification of the physical load in this context [33].…”
Section: Participantsmentioning
confidence: 99%